Macrozooplankton and micronekton abundance (Multinet Maxi) during POSEIDON cruise POS520 - Helena Hauss; Shawn Dove; Henk-Jan T Hoving (PANGAEA, 2025)
Depth stratified samples were collected during RV Poseidon cruise POS520 using a Hydrobios Multinet Maxi (0.5m2 net opening, 9 nets, 2mm mesh size) during oblique tows at a speed of 2-3kn. The net was equipped with flowmeters. Samples were preserved in 4% formaldehzde in seawater solution. In the lab, the wet weight of the total sample was determined and individuals were identified and counted. We report volume-specific higher taxon abundance (ind/100m3) for each depth layer.